Implementing court judgments and arbitral awards re maritime disputes in the Southeast Asia: a comparative analysis - Akisheva, Asylai (Riga Graduate School of Law, 2018)
The paper attempts to address and discuss the issues of implementation of the international judgments and international arbitral awards concerning maritime delimitation in the Southeast Asian region from the point of view of the International Law of the Sea, the ICJ/international arbitration (PCA)/ITLOS practice, case study, and other sources of Public International Law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International arbitration